The effects of pharmaceutical interventions on potentially inappropriate medications in older patients: a systematic review and meta-analysis - Shuang Zhou; Shuang Zhou; Rui Li; Rui Li; Xiaolin Zhang; Yutong Zong; Lili Lei; Zhenhui Tao; Minxue Sun; Minxue Sun; Hua Liu; Ying Zhou; et al. (Frontiers in Public Health, 2023)
IntroductionPotentially inappropriate medications (PIMs) is a particular concern in older patients and is associated with negative health outcomes. As various interventions have been developed to manage it, we performed a systematic review and meta-analysis to evaluate the effect of pharmaceutical interventions on outcomes of PIMs in older patients.MethodsMeta-analysis of eligible randomized controlled trials (RCTs) was conducted to report the outcomes of pharmaceutical interventions in older patients searching from the databases of Cochrane Library, PubMed, Embase, Web of Science, Clinicaltrials.gov, SinoMed and Chinese Clinical Trial Registry (ChiCTR). The PRISMA guidelines were followed and the protocol was registered in PROSPERO (CRD42019134754). Cochrane bias risk assessment tool and the modified Jadad scale were used to assess the risk bias. RevMan software was used for data processing, analysis and graphical plotting.ResultsSixty-five thousand, nine hundred seventy-one patients in 14 RCTs were included. Of the primary outcomes, pharmaceutical interventions could significantly reduce the incidence of PIMs in older patients (OR = 0.51, 95% CI: 0.42, 0.62; p < 0.001), and the number of PIMs per person (MD = -0.41, 95%CI: −0.51, −0.31; p < 0.001), accompanying by a low heterogeneity. Subgroup analysis showed that the application of computer-based clinical decision support for pharmacological interventions could remarkably decrease the incidence of PIMs and two assessment tools were more effective. Of the secondary outcomes, the meta-analysis showed that pharmacological interventions could reduce the number of drugs used per person (MD = -0.94, 95%CI: −1.51, −0.36; p = 0.001) and 30-day readmission rate (OR = 0.58, 95%CI: 0.36, 0.92; p = 0.02), accompanying by a low heterogeneity. However, the pharmaceutical interventions demonstrated no significant improvement on all-cause mortality and the number of falls.ConclusionOur findings supported the efficacy of pharmaceutical interventions to optimize the use and management of drugs in older patients.Systematic review registrationhttps://clinicaltrials.gov/, CRD42019134754.